Analisis Arsitektur Data dalam Database Perusahaan E-Commerce: Studi Kasus Shopee - Dinda Audia Syahira; Muhammad Irwan Padli Nasution (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
The development of information technology has driven the rapid growth of the e-commerce industry. In a digital business environment like Shopee, efficient data management and architecture are key to supporting scalability, transaction speed, and data-based decision making. This study aims to analyze the data architecture used in the Shopee e-commerce platform, including the storage structure, data integration, and processing systems used. This research method is qualitative with a literature study approach and case study analysis based on technical publications and trusted sources. The results show that Shopee adopts a cloud-based distributed data architecture with the use of big data and microservices technology to support operational and analytical needs. The conclusion of this study emphasizes the importance of importance, scalability, and security in data architecture design for modern e-commerce companies.